Military Application of Unmanned Underwater Vehicles: In Quest of A New Legal Regime? - Nainggolan, Jeremia Humolong Prasetya (UI Scholars Hub, 2018)
The Unmanned Underwater Vehicles (UUV) is commonly used for current military operations. There are three legal issues arising out of it, namely (i) legal status; (ii) immunity; and (iii) configuration and rule of the road. The international community has also witnessed the impact of the unregulated UUVs military operation. The article will examined these legal issues in the perspective of international and national law and States practice. To enrich the discussion, legal scholars and practitioners views on UUV will be included. The capability of UUV will also be discussed to increase the comprehension of its role in military operations. Based on existing regulations, either in the international or national law, UUV is not expressly regulated. Furthermore, numerous State react to and/or conduct military application of UUV differently. Hence, it can be suggested that in preventing more incidents, UUVs need to be regulated, either in new regulations or amendment to existing regulation. If it is not possible, states can be urged by the international community and other relevant stakeholders to adopt best standard or practice in their national regulation.